The Language Strategy of Power in the Separation of Case Files through the Concept of the Truth Game - Marbun, Rocky; Sandiana, Erli; Sari, Dellia Rahma (Universitas Muhammadiyah Purwokerto, 2026)
The Criminal Procedure Code provides juridical rights based on the principle of functional differentiation, to the Public Prosecution Service of the Republic of Indonesia to make internal rules that will be implemented by the Public Prosecutor in the trial process of criminal cases. One of the authorities that is technically regulated by the Public Prosecutor's Office is the splitting of case files that contain elements of participation. This legal action is used to obtain witness testimony by confronting the Defendants. This article aims to show the violation of procedural law committed by the Public Prosecutor through its artificial authority in prosecuting criminal cases. The method used is a legal research method with a Trichotomy Relation Approach, namely the concept of Truth-Games based on secondary data. The result is that the Public Prosecutor utilizes internal rules as true knowledge in the form of written language and an Indictment to separate case files. The purpose of this legal action, was so that each defendant provide incriminating testimony against the other, under the shadows of criminal threats if they gave false testimony or refused to testify. Thus, this legal action is a violation of the principle of non-self-incrimination.